Pengaruh Variasi Konsentrasi Na-CMC Terhadap Stabilitas Fisik Gel Ekstrak Pelepah Pisang Ambon (Musa paradisiaca L.) - Yetti Hariningsih (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
Abstract The content of flavonoid in ambon banana extract (Musa paradisiaca L.) is considered responsible for the healing of various injuries. This study aims to determine the effect of Na-CMC variation as a gelling agent on the physical stability of gel ambon banana extract (Musa paradisiaca L.) The method used in this study is to compare Na-CMC concentration in all three formulations. The concentration used is 2,5%, 5,0% and 7,5%. All three formulations will be tested for their physical quality and the best formulation will be tested for physical stability for 4 weeks. The results showed that Formulation II had a good physical quality test based on test results conducted in accordance with the standard. Based on the results of stability test, Na-CMC concentration effect on the spread, the sticky and viscosity with significant value of 0,000. The pH stability test results stated that the Na-CMC concentration did not affect the pH of the preparation with significant value 0,052. Descriptively, organoleptic preparations remain stable from week 0 to week 4. Keywords : Na-CMC variation, ambon banana extract, Gel physical stability.